A historical perspective on patents and industry growth in Finland: Connections and lags - Tuomo Nikulainen (The Research Institute of the Finnish Economy (ETLA), 2008)
This paper aims to establish how the innovative activity in Finland has changed over time in the transition from a resource-driven economy to a knowledge-driven economy. The paper first takes a historical perspective on innovation and industrial activity in Finland through a descriptive analysis. The aim is to identify technological trends in both specific technological areas as well as in different industries. Patent data provides a long time-series of innovative activity from 1842 to 2005 covering 164 years overall. This data is complemented with industry data from 1948 to 2007. The industry data allows a comparative descriptive analysis between the main industries and their respective technological development. The descriptive analysis is complemented with a statistical analysis, in which the interaction between growth in industrial volumes and growth in patent stock is empirically examined taking into account the industry specificities and lag-structures. This approach reveals whether patenting activity, used to approximate innovative activities, can be used to predict the growth of industrial activity. This aspect has received surprisingly little attention in prior research. The regression analyses show that there is a positive connection between industry growth and patent growth. In addition, the patent growth lags, both backward and forward in time, are positively connected to the industrial growth. This finding suggests that there might exist a positive cycle where innovation induces industry growth, which in turn induces innovative activities. Furthermore, patent growth seems to have a weak positive impact on industry growth with a lag of 13 years. This indicates that patent growth might provide weak signals of future industry growth.
Keywords: L60; O11; O14; O33; 330; patents; industry growth; lags; technological change; Patent; Technischer Fortschritt; Industrialisierung; Regression; Lag-Modell; Finnland